UJI DAYA SIMPAN DAN VIABILITAS BENIH KARET (Hevea brasiliensis Muell-Arg.) TANPA CANGKANG TERHADAP KONSENTRASI LARUTAN OSMOTIK DAN LAMA PENGERINGAN - Nikko SeptianFazilla; Charoq Charoq; Rosita Sipayung (Jurnal Agroekoteknologi, 2014)
The seed of rubber is a kind of recalcitrant seeds which is have a low shelf life with the result thatquickly in deterioration so it needed a special treatment in storage period to maintain the seedviability. By using the osmotic solution concentration of Polyethylene Glycol 6000 and seed dryingwhich is very helpful in recalcitrant seed storage due to it has osmotic cell potential to restrict thealteration of water and oxygen capacity in seed. This research aimed to get the optimal of osmoticsolution concentrations and drying time to maintain the seed viability of Rubber. It conducted sinceApril until June 2013 in Laboratory of Plant Breeding, Agriculture Faculty, University of SumateraUtara. The research uses the completely randomized design with two treatments as factor and threereplications. The first factor is osmotic solution concentration of PEG 6000 of PEG 6000 : 0, 15,30, and 45 (% w/v) and other factor is drying period : 0, 4, 8, 12, 16 (hours). The results showed theosmotic solution concentration of PEG 6000 30% w/v significantly in seed growth rateafter storageperiod 3,49% etmal and maximum potential growth 64,22%. 4 hours drying period is the best inseed growth rateup to 3,49 3,89% etmalwith 66,94% maximum potential growth. The osmoticsolution concentrations of PEG 6000 30% w/v and 4-hour drying period is the best combination oftreatments which can seed growth rate up to 3,95% etmal with 66,67% maximum potential growth.Keywords: Rubber seed, osmotic solution concentrations of PEG 6000, drying, seed storage.